A Guidelines for Teacher Competency Management in Lifelong Education at Doi Saket District Learning Encouragement Center, Chiang Mai Province - Muanthae, Kittisak; Pakdee, Chalee; Mahavīro, Asst. Prof. Dr., Phramaha Sakun (MCU Haripunchai Review, 2025)
The objectives of this research were to 1. study and analyze the management of teacher competency in lifelong education at the Doi Saket District Learning Promotion Center, Chiang Mai Province; and 2. develop guidelines for managing teacher competency in lifelong education at the Doi Saket District Learning Promotion Center, Chiang Mai Province. This research was qualitative research using interviews with key informants, including the center director, civil servant teachers, volunteer teachers for non-formal education, and non-formal education teachers, totaling eight people selected purposively, along with group discussions involving eight participants. The research instruments were validated and revised under advisor supervision. Data were analyzed using descriptive and content analysis. The results of the research found that: 1)The analysis of teacher competency management in lifelong education revealed that curriculum creation and development were efficient, starting with appointing a working group composed of all relevant stakeholders. The curriculum aligned with the National Economic and Social Development Plan, the National Education Plan, and the Non-Formal Education Curriculum for Basic Education B.E. 2551, focusing on practical learning, as well as morality, ethics, and professional ethics. 2)The proposed guidelines emphasize competency-based learning design, providing opportunities for learners to participate in learning design and assessment, organizing activities that encourage learner participation at all stages of the learning process, and conducting teaching and learning activities focused on practical application.